Exploring Student Speaking Competence Through Role-Based Differentiated Assessment in Project-Based EFL Learning - Fauziyah, Jihan; Luthfiyyah, Roghibatul; Dwiniasih, Dwiniasih (International Journal of Language Teaching and Education, 2026)
Differentiated assessment has been proposed to accommodate students’ diverse roles and abilities in collaborative speaking activities. However, speaking instruction in many EFL classrooms still relies on memorized dialogues and uniform assessment, limiting fairness and authentic evaluation of communicative competence. Moreover, few studies have integrated Project-Based Learning (PjBL) and differentiated assessment into a role-based speaking assessment framework from students’ perspectives. This study explored the implementation of role-based differentiated speaking assessment in PjBL, students’ speaking performance across communicative roles, their perceptions of the assessment process, and its challenges and benefits. A qualitative case study was conducted with ten senior high school students in an English Club Program in West Java. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using thematic analysis with data triangulation. The findings showed that role-aligned assessment fostered different competencies: fluency, vocabulary, and clarity among presenters, and interactional and facilitation skills among moderators. Students also reported greater confidence, participation, and perceptions of fairness despite speaking anxiety and role-related cognitive demands. This study offers a novel integration of role-based differentiated assessment within PjBL and provides pedagogical implications for more equitable and authentic speaking assessment in EFL classrooms. However, the small sample, single-site English Club context, and focus on only two roles limit the generalizability of the findings.